A reference-grade wild soybean genome - Min Xie (Nature Portfolio, 2019)
Wild relatives of crop plants are invaluable germplasm for genetic improvement. Here, Xie et al. report a reference-grade wild soybean genome and show that it can be used to identify structural variation and refine quantitative trait loci.